Challenges to Jurisprudence Servant of the People or Politics? - Vagharshyan, A. (Bulletin of Yerevan University C: Jurisprudence, 2019)
The article reveals the outhor’s version of the interpretation formula of the “rule of law” and substantiates the thesis that during the period of independence in the Republic of Armenia they missed the task of forming from “homo soveticus” into a “homo juridicus-armenicus” – and especially stable ethical values among lawyers, which leads to their transformation into a servant of politics, perversion of their own professionalism.
Keywords: Law, rule of law, policy, legal thinking, ethics, legality, advisability, constitutionality